HUBUNGAN CHALLENGE STRESS DAN HINDRANCE STRESS TERHADAP PRESENTEEISM PADA KARYAWAN GENERASI Z - Ignacia Callista; Zamralita Zamralita; Ismoro Reza Prima Putra (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The phenomenon of presenteeism, the behavior of continuing to work despite less than optimal physical or psychological condition, poses a significant challenge to the well-being of Generation Z employees, known for their adaptability but vulnerability to stress. This study focuses on analyzing the relationship between two dimensions of work stress—challenge stress (growth-inducing stress) and hindrance stress (inhibiting stress), and levels of presenteeism using Cavanaugh's theoretical framework. Using a quantitative approach using survey methods, data were collected from 209 Generation Z employees in Indonesia using the Challenge and Hindrance-related Self-Reported Stress Scale (C-HSS) and the Job Stress-Related Presenteeism Scale (JSRPS). Statistical analysis revealed the crucial finding that challenge stress significantly negatively correlated with presenteeism, meaning constructive work challenges actually decreased the likelihood of unproductive attendance, while hindrance stress demonstrated a significant positive relationship that triggered this behavior. Additional findings highlighted variations in levels of presenteeism across departments, with divisions with high administrative burdens, such as Accounting, showing the highest levels. This study concludes that effective stress management should focus on increasing meaningful work challenges and minimizing bureaucratic barriers to optimize the productivity and mental health of young workers. ABSTRAK Fenomena presenteeism, yakni perilaku tetap bekerja meski dalam kondisi fisik atau psikologis yang kurang prima, menjadi tantangan signifikan bagi kesejahteraan karyawan Generasi Z yang dikenal adaptif namun rentan terhadap tekanan. Penelitian ini berfokus pada analisis hubungan antara dua dimensi stres kerja, yaitu challenge stress (stres pemicu pertumbuhan) dan hindrance stress (stres penghambat), terhadap tingkat presenteeism dengan menggunakan kerangka teori Cavanaugh. Melalui pendekatan kuantitatif dengan metode survei, data dihimpun dari 209 karyawan Generasi Z di Indonesia menggunakan instrumen Challenge and Hindrance-related Self-Reported Stress Scale (C-HSS) dan Job Stress-Related Presenteeism Scale (JSRPS). Analisis statistik mengungkapkan temuan krusial bahwa challenge stress berkorelasi negatif secara signifikan dengan presenteeism, yang berarti tantangan kerja konstruktif justru menurunkan kecenderungan hadir tanpa produktivitas, sedangkan hindrance stress menunjukkan hubungan positif signifikan yang memicu perilaku tersebut. Temuan tambahan menyoroti variasi tingkat presenteeism antar departemen, di mana divisi dengan beban administrasi tinggi seperti Akuntansi menunjukkan tingkat tertinggi. Studi ini menyimpulkan bahwa manajemen stres yang efektif harus berfokus pada peningkatan tantangan kerja yang bermakna dan meminimalkan hambatan birokrasi untuk mengoptimalkan produktivitas serta kesehatan mental tenaga kerja muda.